EDEN 2.0 greenhouse design study for Neumayer Station III in Antarctica - Kim, Kyunghwan; Schubert, Daniel; Vrakking, Vincent; Bunchek, Jess Marie (2024)
Long-term human planetary exploration hinges on the availability of sustainable life-support systems and food supplies. Bioregenerative life-support systems (BLSS) designed for greenhouses represent a reliable avenue for investigations for current space missions. This system not only generates fresh food by recycling human waste and carbon dioxide but also fosters psychological well-being, mitigating stress for crew members in remote and isolated environments. The EDEN research team at the German Aerospace Center (DLR) has dedicated several years to developing this concept. The initial prototype, known as the EDEN ISS Mobile Test Facility (MTF), was comprised of 20-foot-long high-cube containers deployed about 400 meters from Neumayer Station III (NM-III) on an external platform in Antarctica. This facility was tested from 2015 to 2021 in Antarctica. The success of this MTF paved the way for subsequent projects, such as EDEN NEXT-GEN, EDEN LUNA, and EDEN 2.0. The EDEN 2.0 project's objective is to establish a new greenhouse system within NM-III, remotely monitored and controlled by the Mission Control Center at the DLR Institute of Space Systems in Bremen, Germany. Similar to future planetary greenhouses and habitats, NM-III will provide power, water, data, and waste processing capabilities. A collaborative design study (CE study), a hallmark of DLR's collaborative approach, was conducted in 2022 at the Concurrent Engineering Facility (CEF) in DLR, Bremen, to shape the EDEN 2.0 system design. This paper delves into the collaborative design methodology, and the current status, including design trade-offs, of the EDEN 2.0 project. Additionally, it explores the functional analysis, greenhouse requirements, and the results of Phase A of the system design. Finally, the paper delves into future milestones and their implications for the lunar mission.